2019
DOI: 10.1002/acr.23705
|View full text |Cite
|
Sign up to set email alerts
|

Barriers and Facilitators of Vigorous Cardiorespiratory Training in Axial Spondyloarthritis: Surveys Among Patients, Physiotherapists, and Rheumatologists

Abstract: The identified facilitators and barriers will guide the development of stakeholder-specific implementation strategies. This article is protected by copyright. All rights reserved.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

3
34
0
2

Year Published

2020
2020
2022
2022

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 26 publications
(39 citation statements)
references
References 29 publications
3
34
0
2
Order By: Relevance
“…A larger proportion of participants from SGE classes with a shorter duration were willing to exercise more frequently than participants from classes with a longer duration. This is in line with other studies that have shown that time is an important factor for exercise behavior. Since the present study and a previous study have shown that most patients preferred a personally tailored exercise program in addition to SGE, it might be desirable (from a patient's perspective) to combine relatively shorter SGE with a personal (home) exercise program.…”
Section: Discussionsupporting
confidence: 93%
See 4 more Smart Citations
“…A larger proportion of participants from SGE classes with a shorter duration were willing to exercise more frequently than participants from classes with a longer duration. This is in line with other studies that have shown that time is an important factor for exercise behavior. Since the present study and a previous study have shown that most patients preferred a personally tailored exercise program in addition to SGE, it might be desirable (from a patient's perspective) to combine relatively shorter SGE with a personal (home) exercise program.…”
Section: Discussionsupporting
confidence: 93%
“…The findings of the present study are highly important for a successful implementation of proposed SGE enhancements and are in line with the findings of studies by Niedermann et al , Curbelo Rodríguez et al , and O'Dwyer et al , which endorse the importance of education, periodic reassessments, and monitoring of exercise, as these components are needed to personalize exercise. Including such components in an SGE would require the guiding therapists to specialize in exercise for patients with axial SpA, and patients in the present study viewed this expertise by the SGE guidance as very important.…”
Section: Discussionsupporting
confidence: 91%
See 3 more Smart Citations